2010
DOI: 10.1111/j.1440-1797.2010.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of referral of chronic kidney disease patients to nephrology services (adult)

Abstract: Date written: July 2008 Final submission: February 2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
0
18
0
2
Order By: Relevance
“…[13][14][15][16][17] In fact, patients with an eGFR of 30 mL/min per 1.73 m 2 or less should be referred to a nephrologybased care for appropriate CKD education in order to allow adequate time (at least 3-6 months) for predialysis education. 18,19 This study showed that a program with a nephrologist-based MDC approach could improve clinical renal outcome and reduce medical cost, even for patients with advanced renal failure (eGFR < 15 mL/min per 1.73 m 2 ). Our study demonstrated that most of the stage 5 CKD patients who did not receive MDC underwent incident dialysis therapy with a catheter than those of the stage 5 CKD patients who received MDC.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In fact, patients with an eGFR of 30 mL/min per 1.73 m 2 or less should be referred to a nephrologybased care for appropriate CKD education in order to allow adequate time (at least 3-6 months) for predialysis education. 18,19 This study showed that a program with a nephrologist-based MDC approach could improve clinical renal outcome and reduce medical cost, even for patients with advanced renal failure (eGFR < 15 mL/min per 1.73 m 2 ). Our study demonstrated that most of the stage 5 CKD patients who did not receive MDC underwent incident dialysis therapy with a catheter than those of the stage 5 CKD patients who received MDC.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In the Caring for Australasians With Renal Impairment guidelines, 21 it is recommended that patients with an estimated glomerular filtration rate (eGFR) Ͻ30 mL/min/1.73 m 2 (CKD stage 4) be referred to a nephrology service to give adequate time to prepare for RRT or supportive management and palliative care. 22 A retrospective study of patients with CKD stages 3 and 4 in the United States referred to a nephrology service compared with those who were stage 4 CKD and not referred found that elderly and female patients were less likely to be referred. 23 In addition, for elderly patients, greater comorbidity was a predictor of nonreferral.…”
Section: 17mentioning
confidence: 99%
“…A pesar de eso, no existe un total consenso sobre cuál es el momento exacto para la referencia al nefrólogo. La mayoría concuerda que una TFG menor a 30 mL/min o la presencia de proteinuria son razones suficientes para la referencia (17) . Siguiendo estas consideraciones, gran porcentaje de nuestros pacientes aún no ha requerido una evaluación nefrológica propiamente dicha, lo que ha sido encontrado previamente como una consecuencia de la actual clasificación de la ERC basada en la TFG, donde existe un aumento de consulta nefrológica en situaciones en las que no es requerida (18) , lo cual es de particular importancia en un medio como el nuestro donde existe escasez de nefrólogos (19) .…”
Section: Discussionunclassified